Victims and property victimization in Israel - Mesch, Gustavo (Journal of quantitative criminology, 1997)
Property victimization has increased in recent years in Israel. Apartment burglary and car theft have become a major component in the Israeli public's concern about crime. This paper explores the hypothesis that characteristics of the crime target are central to understanding property victimization. The hypothesis is tested with data from the Third National Israeli Victimization Survey. For apartment burglary, it was found that the larger the number of rooms in the apartment, the higher the risk of victimization. For car theft, it was found that newer cars were more likely to be stolen than older cars. The results shed light on the prominence of property characteristics in the offender's decision-making process and target selection.